Understanding the requirement engineering for organization: the challenges - Haron, Azlena (IEEE, 2012)

(untitled)
This paper explains the challenges that we faced during conducting research in requirement engineering. The aim of the research is to standardize the Requirement Engineering Best Practices Guideline for Software Project in Malaysia Public Sector. Our first step was to define the RE Process, the actors involved as well as their roles. This is followed by the development of RE Best Practices Framework to support the implementation of RE during software requirement specification (SRS) for software project. Finally, the SRS will be presented to the management for the approval. We hope the guideline will help IT Managers in improving their knowledge about RE and increase productivity.